2019
DOI: 10.1038/s41598-019-54354-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Impact of Non-Tectonic Forcing mechanisms on GNSS measured Coseismic Ionospheric Perturbations

Abstract: Global Navigation Satellite System (GNSS) measured Total Electron Content (TEC) is now widely used to study the near and far-field coseismic ionospheric perturbations (CIP). The generation of near field (~500–600 km surrounding an epicenter) CIP is mainly attributed to the coseismic crustal deformation. The azimuthal distribution of near field CIP may contain information on the seismic/tectonic source characteristics of rupture propagation direction and thrust orientations. However, numerous studies cautioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 35 publications
4
40
0
Order By: Relevance
“…This result is consistent with previous works, i.e., the 2003 Tokachi‐Oki earthquake (Rolland et al., 2011), the 2008 Wenchuan earthquake (Zhao & Hao, 2015) and the 2012 Haida Gwaii earthquake (Jin, Jin, & Li, 2017). Because, previous works have shown that the plasma waves cannot propagate perpendicularly to MF lines and CID propagating to equatorward is at smaller angles with MF line and favorable to be detected for long disturbance (Astafyeva et al., 2014; Bagiya et al., 2019; Heki & Ping, 2005). The 2020 Jamacia earthquake occurred in the northern hemisphere, and the detailed information about the geomagnetic field near the epicenter area was obtained using the IGRF model from National Oceanic and Atmospheric Administration (NOAA, https://www.ngdc.noaa.gov).…”
Section: Resultsmentioning
confidence: 96%
“…This result is consistent with previous works, i.e., the 2003 Tokachi‐Oki earthquake (Rolland et al., 2011), the 2008 Wenchuan earthquake (Zhao & Hao, 2015) and the 2012 Haida Gwaii earthquake (Jin, Jin, & Li, 2017). Because, previous works have shown that the plasma waves cannot propagate perpendicularly to MF lines and CID propagating to equatorward is at smaller angles with MF line and favorable to be detected for long disturbance (Astafyeva et al., 2014; Bagiya et al., 2019; Heki & Ping, 2005). The 2020 Jamacia earthquake occurred in the northern hemisphere, and the detailed information about the geomagnetic field near the epicenter area was obtained using the IGRF model from National Oceanic and Atmospheric Administration (NOAA, https://www.ngdc.noaa.gov).…”
Section: Resultsmentioning
confidence: 96%
“…Bagiya et al. (2019) defined a parameter named Non‐Tectonic Forcing Mechanisms which allows to evaluate the joint effect on the quality of the TEC detection of the local geomagnetic field orientation (Geomagnetic field—Neutral wave orientation Factor; GNF), the GNSS network geometry (Satellite Geometry Factor; SGF), and the effects of ambient electron density (Electron Density Factor; EDF) as: NTFM(λ,φ,h)=GNF(λ,φ,h)×EDF(λ,φ,h)×SGF(λ,φ,h) where λ , φ , and h depict the geographic longitude, latitude, and terrestrial altitude respectively.…”
Section: Resultsmentioning
confidence: 99%
“…M. Rolland et al, 2013;Sunil et al, 2015) have investigated the effects of the magnetic field on the propagation of ionospheric disturbances showing an important attenuation of the signal in regions where the perturbation is traveling in the same direction of the magnetic field. Bagiya et al (2019) defined a parameter named Non-Tectonic Forcing Mechanisms which allows to evaluate the joint effect on the quality of the TEC detection of the local geomagnetic field orientation (Geomagnetic field-Neutral wave orientation Factor; GNF), the GNSS network geometry (Satellite Geometry Factor; SGF), and the effects of ambient electron density (Electron Density Factor; EDF) as: 1 and Table 1 for legend reference and terminology. IVPI, ionospheric volcanic power index; VEI, volcanic explosivity index.…”
Section: Gnss-tec and Ivpimentioning
confidence: 99%
“…In addition to fault mapping, our method can be used to estimate earthquake magnitude. The latter can be done by removing non-tectonic impacts introduced by the magnetic field configuration at the epicentral area, LOS geometry factor and the background ionization (Bagiya et al 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%